First champions in tourney - The Star, Y.P. Sivam (2013)
UNIVERSITI Teknologi Malaysia (UTM) became the inaugural champions of the Higher Education Ministry (lPT) Netball League when they defeated Universiti Putra Malaysia (UPM)38- 26 in the final at the UM Sports Centre in Kuala Lumpur recently.